2013
DOI: 10.1209/0295-5075/102/68001
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-driven aggregation in multilamellar membranes

Abstract: Membrane-fluctuation-induced attraction between ligand-receptor sites binding neighboring membranes is studied using meshless membrane simulations and the Weil-Farago two-dimensional lattice model. For the adhesion sites binding two membranes, this entropic interaction is too weak by itself for the adhesion sites to form a large stable domain. However, it is found that this attraction is enhanced sufficiently to induce large domains either when the sites bind three or more neighboring membranes together or hav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…A similar attraction has previously been obtained for the binding sites of two membranes, when the membranes around the binding sites are hardened [56].…”
Section: B Protein Modelsupporting
confidence: 81%
See 1 more Smart Citation
“…A similar attraction has previously been obtained for the binding sites of two membranes, when the membranes around the binding sites are hardened [56].…”
Section: B Protein Modelsupporting
confidence: 81%
“…II, the simulation model and method are described. We simulate membrane tubes and vesicles using an implicit-solvent meshless membrane model [48][49][50][53][54][55][56]. A banana-shaped protein rod is assumed to be strongly adsorbed onto the membrane and the protein and membrane region below it are modeled as a linear string of particles with a bending stiffness and preferred curvature.…”
Section: Introductionmentioning
confidence: 99%
“…A confining surface located at z conf = 6σ completely suppresses thermal undulations, and eliminates the fluctuation mediated interactions between the adhesion bonds. Under these conditions, the threshold value for aggregation increases to [19,21], that the entropic gain of aggregation compensates for, roughly, half of the loss in mixing entropy of the adhesion bonds.…”
Section: A Membranes Under Confinementmentioning
confidence: 99%
“…The fact that adhesion domains do not form for ǫ = 0 implies that the fluctuation entropy gained by the aggregation of the adhesive lipids only partially compensates for their loss of mixing entropy. In another CG simulation study, Noguchi demonstrated that cell junctions connecting more than two membranes can aggregate without an additional attractive potential between them [21]. This observation can be understood because the total entropy of thermal undulations increases linearly with the number of membranes, N m , while the mixing entropy of the cell junctions is independent of N m .…”
Section: Introductionmentioning
confidence: 97%
“…In agreement with previous lattice models that include the membrane explicitly (and not via a potential of mean force) [10][11][12], the adhesion sites do not form large clusters when ǫ = 0, which implies that the membrane-mediated interactions alone are not sufficient to allow the formation of large adhesion domains, but they greatly reduce the strength of the residual interactions required to facilitate cluster formation. Following this study, Noguchi suggested that the strength of the membrane-mediated interactions can be enhanced by pinning more than one membrane to the surface [15]. He demonstrated this by simulating monolayers of particles that are pinned to each other by "gap junctions".…”
mentioning
confidence: 97%